1990
DOI: 10.1161/01.cir.82.6.2003
|View full text |Cite
|
Sign up to set email alerts
|

Beta-adrenergic receptors in lymphocyte subsets after exercise. Alterations in normal individuals and patients with congestive heart failure.

Abstract: Dynamic exercise increases the number of j-adrenergic receptors in mixed lymphocytes by a mechanism that is incompletely understood. In a set of in vivo studies, we have investigated the effects of dynamic exercise on the subset distribution of circulating lymphocytes and on the number of fJ-adrenergic receptors in each of these subsets in two groups of patients. In healthy subjects, exercise increased plasma norepinephrine and epinephrine and caused lymphocytosis. Whereas the number of The,lper cells increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
71
1
6

Year Published

1996
1996
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(82 citation statements)
references
References 31 publications
4
71
1
6
Order By: Relevance
“…They also found no significant alteration in the number of b-ARs in subsets other than natural killer cells after exercise, suggesting that the exercise-induced increase in b-AR of mixed lymphocytes is caused largely by redistribution of circulating cell subsets that differ in b-AR number. They also reported that the observed redistribution of circulating subsets alone can only explain an apparent increase in b-AR of 19% in mixed lymphocytes (23). In general, maximal exercise induces a near doubling of lymphocytic b-ARs, as found in the present study.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…They also found no significant alteration in the number of b-ARs in subsets other than natural killer cells after exercise, suggesting that the exercise-induced increase in b-AR of mixed lymphocytes is caused largely by redistribution of circulating cell subsets that differ in b-AR number. They also reported that the observed redistribution of circulating subsets alone can only explain an apparent increase in b-AR of 19% in mixed lymphocytes (23). In general, maximal exercise induces a near doubling of lymphocytic b-ARs, as found in the present study.…”
supporting
confidence: 86%
“…Maisel et al (23) pointed out that a change in lymphocytic subset composition contributes to the increase in number of lymphocytic b-ARs. They demonstrated that dynamic exercise markedly increases the number of T suppressor/cytotoxic and natural killer cells but only modestly increases the number of T helper cells; T helper cells have few b-ARs, whereas T suppressor/cytotoxic and natural killer cells have a high b-AR content.…”
mentioning
confidence: 99%
“…Lymphoid cells express ␤-AR, and both T and NK lymphocytes express ␤ 2 -AR. Maisel and colleagues (17) have suggested that ␤ 2 -AR density differs among leukocytes with NK cells Ͼ CD14 monocytes Ͼ T cytotoxic cells Ͼ Th cells. Sanders and coworkers (23) have demonstrated that unlike Th1 lymphocytes, Th2 lymphocytes do not express ␤ 2 -AR.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological 49 and physiological stressors are known to result in a significant redistribution of the lymphocyte population and increase the percentage of NK cells 50,51 in adult peripheral blood, probably through activation of the sympathetic nervous system 52,53 and/or the hypothalamic-pituitaryadrenal axis 54 . This phenomenon is mediated, in part, by 55 , including NK cells 56 . Pre-eclampsia could be considered a state of physiological stress for the fetus resulting from chronic uteroplacental deficiency, and this may partially explain the higher percentage of NK cells observed in neonates of pre-eclamptic mothers.…”
Section: Journal Of Maternal-fetal and Neonatal Medicinementioning
confidence: 99%